2004
DOI: 10.1111/j.1468-0408.2004.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of New Public Management Practices on Product Costing and Service Pricing Decisions in Dutch Municipalities

Abstract: New Public Management reforms are aimed at improving effectiveness and efficiency of performance by a great variety of different organisational, managerial and accounting reforms. In the last decade, a great number of the 572 Dutch municipalities have been implementing some NPM reforms, most notably decentralisation of responsibilities to lower organisational levels and restructuring of the budget and financial reports into a product based format. This study comprises a survey among 114 municipalities to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 25 publications
5
43
0
1
Order By: Relevance
“…This results from the multidimensional character of New Public Management as well as from the findings in previous research that in the Netherlands NPM reforms appear not to be implemented by municipalities as a package (e.g. Groot and Budding, 2003). Second, the choice of the departments in this study limits the extent to which the results of this study can be generalized.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This results from the multidimensional character of New Public Management as well as from the findings in previous research that in the Netherlands NPM reforms appear not to be implemented by municipalities as a package (e.g. Groot and Budding, 2003). Second, the choice of the departments in this study limits the extent to which the results of this study can be generalized.…”
Section: Discussionmentioning
confidence: 48%
“…These developments were stimulated by spending cuts, national legislation and the Policy and Management Instruments (PMI) project. 1 However, from previous research we know that there are great differences among the municipalities with respect to the level of implementation of these changes (Groot and Budding, 2003). Furthermore, ter Bogt and van Helden (2000) have shown that there is a wide gap between formal accounting changes and their actual application.…”
Section: Study Design and Methodsmentioning
confidence: 97%
“…Structural reforms, which raise competition between several service providers, could strengthen the case for a wider application of user charges. More generally, user charges are best applied in a framework where providers are competing with each other, where SCG budgets report service revenues and costs in a transparent way and where citizens have some control over the level and structure of charges (Groot and Budding, 2004). In the following, two policy areas are reviewed, where a wider application of user fees could help fiscal consolidation.…”
Section: User Feesmentioning
confidence: 99%
“…For some services such as health care, where consumers are unsure about actual needs and where user fees could induce a spiral of supply-induced demand, SCG may have to set limits on the right of providers to define user fee levels. More generally, some country evidence suggests that user fees are best applied in a framework where providers are competing with each other, where SCG budgets report service revenues and costs in a transparent way and where citizens have some control over fees (Groot and Budding, 2004).…”
mentioning
confidence: 99%
“…Many fiscal equalisation arrangements do not include user fees into the sub-central revenue base, so SCG have some incentives to replace taxes by fees (Groot and Budding, 2004). …”
mentioning
confidence: 99%